Factors influencing the timeliness of care for patients with lung cancer in Bangladesh - Adnan Ansar; Virginia Lewis; Christine Faye McDonald; Chaojie Liu; Muhammad Aziz Rahman (BMC Health Services Research, 2023)
Abstract Background This study explored the factors associated with timeliness of care in the healthcare seeking pathway among patients with lung cancer in Bangladesh. Methods A structured questionnaire was used for data collection from 418 patients with lung cancer through face-to-face interviews in three tertiary care hospitals. Log-rank tests were performed to test differences in the length of intervals between points in healthcare by socioeconomic characteristics and care seeking behaviours of the patients. Cox Proportional Hazard (PH) regression analysis was performed to identify the predictors of the intervals after adjustment for variations in other variables. Results A higher education level was associated significantly (p < 0.05) with a shorter interval between first contact with a healthcare provider (HCP) and diagnosis (median 81 days) and initiation of treatment (median 101 days). Higher monthly household income was associated significantly with a shorter time from first contact and diagnosis (median 91 days), onset of symptom and diagnosis (median 99 days), onset of symptom and treatment (median 122 days), and first contact with any HCP to treatment (median 111 days). Consulting with additional HCPs prior to diagnosis was associated significantly with longer intervals from first contact with any HCP and diagnosis (median 127 days), onset of symptom and diagnosis (median 154 days), onset of symptom and treatment (median 205 days), and first contact with any HCP to treatment (median 174 days). Consulting with informal HCPs was associated significantly with a longer time interval from symptom to treatment (median 171 days). Having more than one triggering symptom was associated significantly with a shorter interval between onset of symptoms and first contact with any HCP. Conclusion The predictors for timeliness of lung cancer care used in this study affected different intervals in the care seeking pathway. Higher education and income predicted shorter intervals whereas consulting informal healthcare providers and multiple providers were associated with longer intervals.